Association Between Subscapularis Trigger Point and Frozen Shoulder: A Cross Sectional Study - Rabia Shaikh, Fakhrah Safdar, Asif Gulzar Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Uncertainty surrounds the relationship between subscapularis trigger sites and the development of frozen shoulder syndrome. Objectives: The purpose of this study was to investigate the relationship between subscapularis trigger points and immobilized shoulder in patients from the Outpatient Physical Therapy Department at NMC Hyderabad. Methods: This cross-sectional study was conducted from September 2022 to February 2023 and included 71 patients diagnosed with grade 1 or 2 frozen shoulder based on Codman’s criteria and aged 35 or older. Using an axillary approach, subscapularis trigger points were identified manually, and their presence was evaluated on both the affected and unaffected sides. Using the Chi-square test in SPSS version 22, the relationship between subscapularis trigger points and immobilized shoulder was analyzed. Results: 33 (46.5%) of the 71 participants were male, while 38 (53.5%) were female, with a mean age of 53.32 years. On the affected side, there was a significant association between frozen shoulder and subscapularis trigger points (p =.001). Intriguingly, a statistically significant difference was also observed in the unaffected shoulder joint (p =.001). Practical Implications: It highlighted the importance of diagnosing and treating subscapularis trigger points in patients with frozen shoulder, potentially guiding new therapeutic strategies to improve shoulder mobility and reduce pain in these individuals. Conclusion: Our findings indicate a considerable association between subscapularis triggers points and frozen shoulder, making these trigger points possible therapeutic targets. To investigate the underlying mechanisms and validate these results in larger populationss, additional research is required. Keywords: Frozen shoulder syndrome; Orthopedics; Subscapularis trigger points; Surgery